2021
DOI: 10.1016/j.combustflame.2021.111426
|View full text |Cite
|
Sign up to set email alerts
|

A tangent linear approximation of the ignition delay time. I: Sensitivity to rate parameters

Abstract: A tangent linear approximation is developed to estimate the sensitivity of the ignition delay time with respect to individual rate parameters in a detailed chemical mechanism. Attention is focused on a gas mixture reacting under adiabatic, constant-volume conditions. The uncertainty in the rates of elementary reactions is described in terms of uncertainty factors, and are parametrized using independent canonical random variables. The approach is based on integrating the linearized system of equations governing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 43 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…Recently, however, several approaches [9][10][11][12] have been conducted that focus on exploring alternative means of estimating sensitivities that can specifically reduce the O(N ) cost associated with the brute force approach. These include methodologies based on tangent linear approximations [9,[12][13][14], adjoint techniques [10], as well as optimization approaches [11]. Applications in [9][10][11][12] have particularly focused on estimating ignition delay time sensitivities to rate parameters.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, however, several approaches [9][10][11][12] have been conducted that focus on exploring alternative means of estimating sensitivities that can specifically reduce the O(N ) cost associated with the brute force approach. These include methodologies based on tangent linear approximations [9,[12][13][14], adjoint techniques [10], as well as optimization approaches [11]. Applications in [9][10][11][12] have particularly focused on estimating ignition delay time sensitivities to rate parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These include methodologies based on tangent linear approximations [9,[12][13][14], adjoint techniques [10], as well as optimization approaches [11]. Applications in [9][10][11][12] have particularly focused on estimating ignition delay time sensitivities to rate parameters. These works have shown that the underlying techniques offer accurate and efficient means of estimating sensitivities and that, in high dimensional situations, speedup by order-of-magnitude can be achieved over the traditional brute-force finite-difference approach.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations